Mucosal-associated bacterial flora of the intestine in patients with Crohn's disease and in a control group. Issue 11 (November 1978) - Peach, Susan; Lock, M. R.; Katz, D.; Todd, I. P.; Tabaqchali, Soad
Abstract : The bacterial flora intimately associated with the intestinal mucosa of patients with Crohn's disease has been examined and compared with the mucosal flora of a control group. Specimens were obtained at operation from patients undergoing intestinal surgery. Whole thickness intestinal sections were taken from the diseased segment and from a portion of uninvolved intestine from patients with Crohn's disease as well as from a control group. A section of each specimen was examined histologically. Twenty-two specimens of Crohn's tissue (12 ileum, 10 colon) and 46 control samples from small and large bowel were examined using strictly anaerobic bacteriological techniques in an anaerobic chamber. Organisms were grown under both aerobic and anaerobic conditions. A mucosal flora was found to exist in all the large bowel samples and in three-quarters of the small bowel samples. It was qualitatively similar in all the samples, consisting mainly of Gram positive bacteria, aerobic Gram negative rods and bacteroides. Greater numbers of bacteria were associated with colonic tissue (10 7 - 10 8 per g) than with tissue from the jejunum (10 3 - 10 4 per g). This difference was statistically significant (p<0·03). Samples from the terminal ileum were quantitatively intermediate between jejunum and colon. There was no statistical difference in the numbers of bacteria associated with Crohn's tissue compared with histologically normal tissue from the same patients and from the control group of patients. Among the bacterial isolates, however, Enterobacteria were more commonly associated with Crohn's tissue.